Al-Amthāl al-Muṣarraḥah fī al-Suwar al-Madaniyyah (Dirāsah Taḥlīliyyah Balāghiyyah) - Abdurrahman Abdurrahman (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2017)
Before discussing the parables in the Holy Qur'an, their remarkable rhetorical imagery, elevated literary styles, eloquent miraculousness, noble objectives, honorable purposes, and lofty aims, it is appropriate to first speak about the eternal Book of Allah, whose verses encompass these parables as one of the manifestations of its artistic and literary inimitability. Qur'anic parables play a significant role in Islamic da'wah because they represent one of the divine means of guidance, direction, instruction, and education. They encourage people to perform righteous deeds, inspire them to uphold virtue, and warn them against disbelief and evil.